HYBRID TONGUES: CODE-SWITCHING AND LEXICAL BORROWING UZBEK ENGLISH RUSSIAN MULTILINGUAL LANGUAGES - Adiba Kasimova,; Abduvaliyeva Ma’mura, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract:  This  article  examines  the  phenomenon  of  hybrid  language  use  in Uzbekistan,  focusing  on  code-switching  and  lexical  borrowing  in  Uzbek–English–Russian multilingual contexts. Drawing on concepts from Sociolinguistics, the study analyzes structural patterns, communicative functions, and sociocultural motivations of  multilingual  speech.  It  demonstrates  that  code-switching  and  borrowing  are systematic and meaningful processes that reflect speakers’ linguistic competence and adaptability.  The  findings  suggest  that  hybrid  language  practices  are  not  signs  of linguistic decline but rather indicators of dynamic language evolution in response to globalization, technological development, and cultural interaction.